Ethical dilemmas of aesthetic medicine: Between restorative medicine and the commercialisation of the body - Wieczorkowska, Magdalena (Annales. Etyka w Życiu Gospodarczym, 2019)
Technological advances in medicine have given the sick and the disabled a chance of making a full recovery. However, contemporary trends show that medicine goes far beyond its restorative functions. The increasing popularity of plastic surgery raises many questions. Is medicine beginning a new era of its development as a response to the commercialisation of the human body? Does not correcting nature lead to people’s segregation into the better and the worse ones? The development of medical technologies has accelerated the commercialisation of the body by treating it as a package that one can “redecorate” to be more attractive in the market of social relations. Plastic surgery is trying to solve the identity crisis and psychological problems of people. New forms of medicalisation are emerging. A lack of success is seen as a symptom of a disease that can be cured with a scalpel. Plastic surgery can be a tool of reconstruction of one’s identity but only under strict circumstances (genetic defects, bodily injuries). By posturing as a solution to people’s psychological and sociological problems, medicine must reckon with a moral/ethical critique.